2012
DOI: 10.1007/s12094-012-0875-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the factors of lateral lymph node metastasis in papillary microcarcinoma of the thyroid in eastern China

Abstract: When the evaluation for lateral lymph nodes from a preoperative approach is inadequate or not obvious, our scoring system for prediction of lateral LNM can be another choice. Patients with clinicopathological and US index points ≤ 2 could be considered as lateral LNM negative, so more diagnostic approach is recommended for patients with clinicopathological and US index points >2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 29 publications
1
27
4
3
Order By: Relevance
“…However, the univariate and multivariate analyses confirmed tumor size >5 mm as an independent predictor of LNM. A number of previous studies reported the upper pole location as an independent predictive factor for lateral LNM (23,29). To the best of our knowledge, few reports have defined the statistical correlation between tumor location and CLNM in PTMC.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the univariate and multivariate analyses confirmed tumor size >5 mm as an independent predictor of LNM. A number of previous studies reported the upper pole location as an independent predictive factor for lateral LNM (23,29). To the best of our knowledge, few reports have defined the statistical correlation between tumor location and CLNM in PTMC.…”
Section: Discussionmentioning
confidence: 96%
“…TTD >10 mm were independent predictors for CLNM from the multivariate analysis. Zeng et al (23) indicated that certain US characteristics (upper pole location, no well-defined margin and presence of calcifications) were predictive factors for lateral LNM in patients with PTMC in Eastern China. Few studies have reported the associations between US characteristics and CLNM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that the presence of clinical lymph node metastasis in PTMC was one of the most important prognostic indicators, whereas others demonstrated that pathological lymph node metastasis identified following prophylactic dissection did not significantly affect patient prognosis. Pathological lymph node metastasis from PTMC was found in a range of 26-56% (15)(16)(17)(18)(19)(20). The reason(s) for the difference between clinical and pathological lymph node metastasis have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…По данным литерату-ры, метастатическое поражение лимфоузлов было выявлено в 25-30% случаев [34,[43][44][45][46][47][48].…”
Section: микрокарциномы с метастатическим поражением лимфоузловunclassified
“…Несколько исследователей сообщили, что наличие метастазов в лимфатические узлы при микрокар-циномах является одним из наиболее важных про-гностических факторов, тогда как другие считают, что поражение лимфатических узлов существенно не влияет на прогноз пациента. Метастатическое пора-жение лимфоузлов при микрокарциномах было вы-явлено в 26-56% случаев [43][44][45][46][47][48].…”
Section: агрессивное лечение микрокарцином или их агрессивное течение?unclassified